Community resilience, land degradation and endogenous lock-in effects: evidence from the Alento region, Campania, Italy. Issue 3 (3rd March 2016) - Wilson, Geoff; Quaranta, Giovanni; Kelly, Claire; Salvia, Rosanna
Abstract : This study analyses social, economic and political "lock-ins" for understanding community resilience and land degradation. The study focuses on lock-ins from within communities, using four case study communities in Italy affected by land degradation. The analysis highlights the complex interrelationships between various lock-ins, and suggests that the communities are on declining resilience pathways that may lead to increasing difficulties in addressing land degradation issues in future.